2016
DOI: 10.1101/030239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive Cross-Population Analysis of High-Grade Serous Ovarian Cancer Supports No More Than Three Subtypes

Abstract: Four gene expression subtypes of high-grade serous ovarian cancer (HGSC) have been previously described. In these early studies, a fraction of samples that did not fit well into the four subtype classifications were excluded. Therefore, we sought to systematically determine the concordance of transcriptomic HGSC subtypes across populations without removing any samples. We created a bioinformatics pipeline to independently cluster the five largest mRNA expression datasets using k-means and nonnegative matrix fa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…This large-scale analysis confirmed the previously described mesenchymal (s1.MES), immunoreactive (s2.IMM), and proliferative (s3.PRO) subtypes as distinct entities. While our work was in progress, a cross-population analysis has also confirmed at least mesenchymal and proliferative subtypes were stable through clustering comparisons across individual expression studies (31). In the present study, a new subtype “anti-mesenchymal” (s5.ANM) was derived from TCGA-differentiated/Tothill-C4 subtype, with noticeable down-regulation of mesenchymal signature genes and better survival outcomes in both the public and Mayo Clinic HGSOC cohorts.…”
Section: Discussionmentioning
confidence: 59%
“…This large-scale analysis confirmed the previously described mesenchymal (s1.MES), immunoreactive (s2.IMM), and proliferative (s3.PRO) subtypes as distinct entities. While our work was in progress, a cross-population analysis has also confirmed at least mesenchymal and proliferative subtypes were stable through clustering comparisons across individual expression studies (31). In the present study, a new subtype “anti-mesenchymal” (s5.ANM) was derived from TCGA-differentiated/Tothill-C4 subtype, with noticeable down-regulation of mesenchymal signature genes and better survival outcomes in both the public and Mayo Clinic HGSOC cohorts.…”
Section: Discussionmentioning
confidence: 59%
“…A recent analysis of genotyping accuracy has raised questions about the quality of sequencing-based variant calls in TCGA’s HGSC samples [76] which may affect the findings in Hofree et al [75]. Given the exploratory nature of molecular clustering and limitations of the approaches used, more research is needed about how many underlying molecular subtypes exist [7779] and if they are consistent across populations [80]. …”
Section: Characteristics Of Hgsc Molecular Subtypesmentioning
confidence: 99%
“…While previous reports have described four HGSC subtypes, the multi-population study suggested that the number was three or fewer 26 . Given these conflicting results, we applied community detection to HGSC subtype-specific gene lists previously derived from results classifying 2, 3, and 4 subtypes 26 . Because this is an analysis of cancer genomics data, we used cancer pathways from the Pathway Interaction Database (PID) 5 .…”
Section: Methodsmentioning
confidence: 74%
“…We previously derived these gene lists from a differential expression analysis across HGSC subtypes that were concordant across different populations 26 . We selected only the top performing algorithms from our simulation study, Walktrap and Multilevel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation